2015
DOI: 10.18632/oncotarget.6063
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial TGF-β attenuation with paclitaxel inhibits the epithelial-to-mesenchymal transition and breast cancer stem-like cells

Abstract: Distant relapse after chemotherapy is an important clinical issue for treating breast cancer patients and results from the development of cancer stem-like cells (CSCs) during chemotherapy. Here we report that blocking epithelial-to-mesenchymal transition (EMT) suppresses paclitaxel-induced CSCs properties by using a MDA-MB-231-xenografted mice model (in vivo), and breast cancer cell lines (in vitro). Paclitaxel, one of the cytotoxic taxane-drugs such as docetaxel, increases mesenchymal markers (Vimentin and Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 59 publications
5
74
0
Order By: Relevance
“…Paclitaxel caused non-significant increase in CSCs percentage in both cell lines as compared with the control. Our finding of increased CSCs percentage after paclitaxel alone treatment corresponds to finding by others 26. Combined treatment with paclitaxel and compound 1 abolished the effect of compound 1 in reducing CSCs with paclitaxel increasing CSCs more efficiently than the decrease induced by compound 1 .…”
Section: Resultssupporting
confidence: 91%
“…Paclitaxel caused non-significant increase in CSCs percentage in both cell lines as compared with the control. Our finding of increased CSCs percentage after paclitaxel alone treatment corresponds to finding by others 26. Combined treatment with paclitaxel and compound 1 abolished the effect of compound 1 in reducing CSCs with paclitaxel increasing CSCs more efficiently than the decrease induced by compound 1 .…”
Section: Resultssupporting
confidence: 91%
“…For example, in breast cancer the EMT state has been associated with cancer stem cell properties including the expression of stem cell-associated CD44+/CD24-/low antigenic profile, self-renewal capabilities and resistance to conventional therapies [3436]. Our previous study has shown that mesenchymal-derived osteosarcoma did not express epithelial markers, however, osteosarcoma stem cells express more mesenchymal markers and showed higher motility [13].…”
Section: Discussionmentioning
confidence: 99%
“…HIF1α increases expression levels of NOXs, which results in ROS generation [59,60], regulating the transcriptional activity of HIF1α and driving the EMT [46,61]. In addition, ROS generation induces Snail expression, subsequently leading to the EMT [62,63] This study also showed that HIF1α increased ROS generation via NOX4 and demonstrated that ROS induced the EMT by inducing Snail expression in the livers of BDL rats and LX-2 cells (Fig. 5 and 6).…”
Section: Discussionmentioning
confidence: 99%